2014
DOI: 10.1002/jbm.a.35338
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐textured fluidic biochip as biological filter for selective survival of neuronal cells

Abstract: This is an innovative study to engineer biological filter to evaluate the effect of template surface structure and physiochemical properties that can be used for wide variety of applications in biological, health care as well as environmental protection. Specifically, planar silicon (Si) wafer and arrayed Si nano-tips (SiNT) templates were fabricated and coated with gold for various lengths of time to study the effect of surface charge, surface roughness, and hydrophilicity on biological activity of rat pheoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Yamada et al reported that mild electrical stimulation strongly influences embryonic stem cells to assume neuronal fate [11]. Han et al influences the cell more than the wettability and roughness of the substrate [12]. As an extension of their observation, the researchers have acknowledged that the differentiation of stem cells under the influence of external cues can open up possibilities for studying novel mechanisms underlying cellular differentiation and more importantly, suggested the possibilities for adaption in clinical contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al reported that mild electrical stimulation strongly influences embryonic stem cells to assume neuronal fate [11]. Han et al influences the cell more than the wettability and roughness of the substrate [12]. As an extension of their observation, the researchers have acknowledged that the differentiation of stem cells under the influence of external cues can open up possibilities for studying novel mechanisms underlying cellular differentiation and more importantly, suggested the possibilities for adaption in clinical contexts.…”
Section: Introductionmentioning
confidence: 99%
“…A separation of ∼2 μm between cell-repulsive PEG hydrogels is enough to guide neurite growth and inhibit astrocyte adhesion and growth . Nanostructure and nanofluidic transport used by Han et al selectively enhance survival of neuronal cells . Human embryonic stem cells (hESCs) are differentiated into neurons by ridge/groove patterns .…”
Section: Target Cells For Tissue Regenerationmentioning
confidence: 99%
“…For these reasons, researchers are driven to find and design synthetic and more feasible solutions, such the development of polymeric biomaterials, 3D-bone implants and biodegradable devices [5][6][7][8]. Furthermore, great attention continues to be directed to the development of new technologies, such as surface modification techniques, to increase the actual clinical performance of implant devices [9,10]. Orthopaedic biomaterials are designed to be implanted in the human body as components of devices for replacing or repairing various tissues such as bone, cartilage or ligaments and tendons, and even to direct and guide bone restoration when necessary.…”
Section: Introductionmentioning
confidence: 99%